THE SEQUENCE OF PHASE TRANSFORMATIONS DURING THE CRYSTALLIZATION MATERIAL WITH COMPOSITION Sr2FeMoO6-δ FROM PRECURSORS - N. A. Kalanda; S. A. Kovaleva; L. S. Lobanovskiy; L. I. Hurski; M. V. Yarmolich (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The sequence of phase transformations during Sr2FeMoO6-d crystallization by solid phase method was studied for powders synthesized from the stoichiometric mixture of SrFeO3- x and SrMoO4 precursors. It was found that the synthesis of strontium ferromolybdate solid solution proceeds through a series of parallel chemical reactions. Reveals that at the beginning stage of interaction the initially formed Sr2FeMoO6-δ powder is enriched with iron. During the annealing process, the composition of strontium ferromolybdate changes and the molybdenum content increases upon further heating. It was found that the use of precursors reduces the annealing temperature.